BIOM-39. ESTABLISHMENT OF A CONNECTIVITY SIGNATURE FOR GLIOMAS - Kessler, Tobias (Neuro Oncol, 2020)
Recent studies have demonstrated extensive cell-to-cell connectivity between tumor cells of gliomas with considerable relevance for tumor progression and therapy resistance. Tumor microtubes (TMs) are neurite-like tumor cell extensions that build these tumor cell networks. Measuring the extent of connectivity in individual tumors has been challenging and depended on anatomical parameters that are difficult to evaluate in patient samples. We performed bulk and single-cell (sc)RNA sequencing of connected vs. unconnected tumor cells from patient-derived xenograft tumors using a newly developed technology that exploits SR101 dye transfer within tumor cell networks. scRNA sequencing was performed with 17 human glioblastoma tumor samples. Three diffuse glioma cohorts from The Cancer Genome Atlas (n = 648), the Chinese Glioma Genome Atlas (n = 668) and the NCT Neuro Master Match (n = 38, IDH-wildtype only) were used to assess clinical properties. A connectivity signature both from bulk and scRNA sequencing data of xenografted primary glioblastoma tumor cells was established. Comparative analysis showed better performance and higher biological relevance of the single-cell derived signature that involves 71 genes. Most of the genes are related to neurogenesis and neural tube development, including several previously recognized TM-relevant genes. Highest connectivity was observed in astrocytic-like and mesenchymal-like tumor cells. Induction of connectivity in vitro was accompanied with increase of the connectivity signature. The connectivity signature was higher in astrocytic as compared to oligodendrocytic gliomas, and highest in IDH-wildtype gliomas. In accordance, connectivity correlated strongly with dismal survival in all three glioma cohorts. The connectivity signature established here is biologically plausible and associates with prognostically relevant glioma subtypes. It provides the first proof-of-principle that tumor cell connectivity is relevant for the clinical course of patients with gliomas, and at the same time serves as a robust biomarker that can be used for future studies, including prospective clinical trials.